Experience of human rights violations and subsequent mental disorders – a study following the war in the Balkans - Priebe, Stefan; Bogić, Marija; Ashcroft, Richard; Frančišković, Tanja; Galeazzi, Gian Maria; Kučukalić, Abdulah; Lečić-Toševska, Dušica; Morina, Nexhmedin; Popovski, Mihajlo; Roughto, Michael; Schüttzwol, Matthiass; Ajduković, Dean (2010)
Context War experiences are associated with substantially increased rates of mental disorders, particularly Post-Traumatic Stress Disorder (PTSD) and Major Depression (MD). There is only limited evidence on what type of war experiences have particularly strong associations with subsequent mental disorders. Objectives To investigate the association of violations of human rights (HR), as indicated in the 4th Geneva Convention, with rates of PTSD and MD and levels of posttraumatic stress symptoms, and compare these with the associations of other stressful war experiences. Design, Setting, and Participants In 2005/6, war affected community samples were recruited in five Balkan countries (Bosnia-Herzegovina, Croatia, Kosovo, Macedonia, Serbia) using a random walk approach. Refugees in three Western European countries (Germany, Italy, United Kingdom) were contacted through registers, community organisations and snowballing. Main Outcome Measure Life Stressors Scale – Revised, MINI International Neuropsychiatric Interview, Impact of Event Scale – Revised. Results 3313 participants in the Balkans and 854 refugees were assessed. Participants reported on average 2.3 of each HR violations and other stressful war experiences. The prevalence rate for PTSD and MD was each 22.8%. Most war experiences increased the risk for both PTSD and MD. When the number of HR violations and other stressful experiences were considered in one model, both were associated with higher risks for PTSD (relative risk [RR], 1.15 ; 95% confidence interval [CI], 1.12-1.18 and 1.21 ; 95%CI, 1.17-1.25, respectively) and higher levels of symptoms of intrusion (coefficient, 1.26 ; 95% CI, 1.11-1.41 and coefficient, 1.44 ; 95% CI, 1.26-1.62, respectively), avoidance (coefficient, 1.12 ; 95% CI, 0.98-1.25 and coefficient, 1.25 ; 95% CI, 1.08-1.41, respectively) and hyperarousal (coefficient, 1.01 ; 95% CI, 0.90-1.12 and coefficient, 1.14 ; 95% CI, 1.01-1.28, respectively). However, only the number of HR violations, and not of other stressful war experiences, increased the risk for MD (RR, 1.16 ; 95% CI, 1.12-1.19 and RR, 1.03 ; 95% CI, 0.99-1.07, respectively). Conclusions Different types of war experiences are associated with increased prevalence rates of PTSD and MD more than 5 years. As compared to other stressful war experiences, the experience of HR violations similarly increases the risk of PTSD, but appears more important for MD.
Projekt MZOS
Projekt MZOS
ENG